FACTORS RELATED TO MEDICATION COMPLIANCE IN DIABETES MELLITUS PATIENTS AT THE PERUMNAS HEALTH CENTER, KENDARI CITY - Ariyanti, Ariyanti (Universitas Halu Oleo, 2024)
ABSTRACT The prevalence of diabetes mellitus in Indonesia who live in urban areas is 10.6% or 8.4 million people. The high incidence of diabetes mellitus requires diabetes patient compliance to take diabetes medication. However, in reality there are still many patients who have low levels of compliance in carrying out medication management programs. This study aims to determine the factors associated with compliance with taking medication for diabetes mellitus patients at the Perumnas Health Center in Kendari City. This study used a cross-sectional design with a sample size of 56 patients taken using a simple random sampling technique. The instrument used to measure research variables uses a questionnaire that has been tested for validity and reliability. Data analysis used the chi-square test with a confidence level of 95%. The research results show education (p-value=0.025), knowledge (p-value=0.004), self-motivation (p-value=0.013), family support (p-value=0.000), support from health workers (p-value=0.001). This means that education, knowledge, self-motivation, family support and support from health workers are related to the level of compliance of diabetes mellitus patients in taking medication. It is recommended for health centers to supervise patients when taking medication, and for the patient's family to remind patients to always take medication. Keywords: Medication Adherence, Diabetes melitus, self-motivation, health support